Pengaruh Modal Minimum Terhadap Minat berinvestasi di Pasar Modal Syariah Dengan Edukasi Sebagai Variabel Moderating (Studi Empiris Mahasiswa Fakultas Keislaman Universitas Trunojoyo Madura) - Sofy Laila Sari; Dahruji Dahruji (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Sharia Investment Gallery is a place for students to learn about investing in the Islamic capital market. There are several programs carried out by the Sharia Investment Gallery, namely educating and motivating students by holding activities such as studies on the Islamic capital market, Islamic capital market schools (SPMS) and also socializing the existence of a minimum capital of IDR 100,000 in opening an account on the market. Islamic capital in order to attract students to invest in the Islamic capital market. Therefore this research is to find out whether Minimum Capital affects students' interest in investing in the Islamic capital market with education as a moderating variable. This research is a quantitative study, the variables used are minimum capital (X), Education (Z), and Student interest in investing (Y). This study tested the MRA interaction. By distributing 131 questionnaires to GIS investors at the Islamic Faculty of Trunjoyo Madura University. The results of this study indicate that the results of the T test on the minimum capital variable affect students' interest in investing in the Islamic capital market. Furthermore, in the interaction test, the education variable has a significant effect in moderating the relationship between minimum capital and interest in investing, and it can be said that the moderating variable (education) strengthens the relationship between minimum capital and investment interest. And included in the pseudo moderation variable (Quasi Moderation.